PENERAPAN DISCOVERY LEARNING UNTUK MENINGKATKAN EFIKASI DIRI DAN HOTS PADA TEMA DAERAH TEMPAT TINGGALKU SISWA KELAS IV A MIN 1 KOTA BENGKULU - Sumini SUmini SUmini; Endang Widi Winarni; Irwan Koto Koto (Universitas Bengkulu, 2020)
The objectives of this research to improve students’ selff efficacy and HOTS. This research was a classroom action research done in 3 cycles performed, each cycle was consist of four stages namely: planning, acting, observing, and reflecting. The action research was done in class IVA, consist of 34 students, 16 female students, and 18 male students. The data were collected by an observation sheet, a questionnaire, and a test of HOTS. Then, the data were analyzed by avarage, percentage, and classification. The results of research showed that the teaching activity, self efficacy, HOTS were improved, and discovery learning effectively improve students’ HOTS. Reccomendation of this research were: 1) the teachers should guide and correct the students’ work, then encourage, reinforcement, even giving reward to students; 2) the teachers should direct the students to develop the knowledge to the environment activity, and inrease references; 3) the teachers should guide the students to connect the answers to their daily experiment; and 4) for the further research, reccommended to conduct the spesific about ability of students’ to answer the question by creation using discovery learning.